Autoconcepto de los estudiantes y su impacto en la toma de decisiones de una carrera universitaria - Ramón Gadñay, Karen Lizbeth (Machala: Universidad Técnica de Machala, 2023)
The present research aims to understand the importance of self-concept and cognitive variables in the decision-making process of a university career. It is sustained under the bases of the Cognitive approach, which maintains those factors that are involved in the growth and development of the mind. In addition, it was established as a single subject of analysis, Self-concept and cognitive variables in the decision-making process of a university career, composed of six categories which are, Skills and abilities, Physical or personality attributes, Exploration and valuation in participation of events, Social and family roles played, Personal goals, Expectations and beliefs about the career. We had the participation of two young people, who had the ideal profile for the study, since both are students of the Technical University of Machala, they are in their first semester of their career, their ages are between 17-18 years old and they voluntarily chose their current university career. This is a qualitative research of phenomenological- hermeneutic design, and has a non-probabilistic-homogeneous sample. To collect the information, instruments used were, the semi-structured interview, which consists of an organized conversation guided by the new information obtained as the interview develops, and qualitative observation, used to directly capture what was exposed by the environment. Within the results, it was evidenced that the skills of the participants are strongly linked to their tastes, in addition, confidence in their physique is evident, and the personological traits influenced them to choose a career that exploits the uniqueness of their characteristics, including the exploration of different events academic and labor, in addition to their performance in family and social roles that benefit the self-concept, personal goals are shown as motivators for the chosen career, finally, expectations and beliefs around the career are presented from a more realistic plane, and increase the sense of success and execution of activities.
La presente investigación tiene como objetivo comprender la importancia del autoconcepto y las variables cognitivas en la toma de decisiones de una carrera universitaria. Está sustentado bajo las bases del enfoque Cognitivo, que mantiene aquellos factores que se involucran en el crecimiento y desenvolvimiento de la mente. Además, se estableció como tema único de análisis: Autoconcepto y variables cognitivas en la toma de decisiones de una carrera universitaria, compuesto por seis categorías que son, Habilidades y destrezas, Atributos físicos o de personalidad, Exploración y valoración en participación de eventos, Roles sociales y familiares desempeñados, Metas personales, Expectativas y creencias en torno a la carrera. Se tuvo la participación de dos jóvenes, que contaban con el perfil idóneo para el estudio, pues ambos son estudiantes de la Universidad Técnica de Machala, están cursando su primer semestre de carrera, sus edades se encuentren entre los 17-18 años y eligieron voluntariamente su actual carrera universitaria. Esta investigación es cualitativa de diseño fenomenológico-hermenéutico, y posee una muestra no probabilística-homogénea. Para recolectar la información se utilizaron instrumentos como, la entrevista semiestructurada, que consiste en una conversación organizada y guiada por la nueva información obtenida a medida que se desarrolla la entrevista, y la observación cualitativa, usada para captar directamente lo expuesto por el entorno. Dentro de los resultados, se evidenció que las habilidades de los participantes están fuertemente vinculadas con sus gustos, además, es evidente la confianza en su físico, y los rasgos personológicos influyeron a elegir una carrera que explote la unicidad de sus características, incluyendo la exploración de diferentes eventos académicos y laborales además de su desempeño en roles familiares y sociales que benefician al autoconcepto las metas personales se muestran como motivadoras para la carrera elegida finalmente, las expectativas y creencias en torno a la carrera se presentan desde un plano más realista, y aumentan el sentido de éxito y ejecución de las actividades.
Keywords: AUTOCONCEPTO; FACTOR; COGNITIVO; ELECCION DE CARRERA